2006
DOI: 10.1111/j.1463-5224.2006.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

The phenol red thread tear test in large Psittaciformes

Abstract: Results suggest that the PRT tear test is a practical method for measuring tear production in large Psittaciformes, although adaptations to the established diagnostic method are necessary to overcome some anatomical differences present in birds. Good reproducibility of the PRT tear test could not be demonstrated in a clinically normal population of birds but geographic location appears to significantly influence results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
6
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(72 citation statements)
references
References 8 publications
4
61
6
1
Order By: Relevance
“…Although this test is well tolerated by birds (Bliss et al 2015), low reproducibility has been reported in large Psitacciformes (Holt et al 2006), and better PRT reproducibility on A. ventralis (Storey et al 2009). …”
Section: Discussionmentioning
confidence: 93%
“…Although this test is well tolerated by birds (Bliss et al 2015), low reproducibility has been reported in large Psitacciformes (Holt et al 2006), and better PRT reproducibility on A. ventralis (Storey et al 2009). …”
Section: Discussionmentioning
confidence: 93%
“…Some investigators have used the phenol red thread (PRT) tear test for measuring tear production in birds. 6,14 The PRT tear test is an alternative method of tear measurement by which tear production is measured using a 75-mm-long cotton thread that has been impregnated with 1 ll of phenolsulfonphthalein, a pH-sensitive indicator. When the more alkaline tears are absorbed, the pH indicator turns the thread from yellow to red.…”
Section: Discussionmentioning
confidence: 99%
“…The shorter time required to perform the PRT tear test and the small size of the thread may make this test particularly suitable for use in birds and other small animals. 3,6 In the present investigation, the commonly available Schirmer tear strips were used, because these birds have considerably large eyes and placement of conventional Schirmer tear strips in these birds is practically possible without difficulty.…”
Section: Discussionmentioning
confidence: 99%
“…6 Reference ranges for intraocular pressure and tear productions have not been reported for any species in the family Anatidae. Measurement of tear production has been performed in different avian species including penguins, 7,8 owls 9,10 European birds of prey, 11 vultures, 12 ostrich, 13 bald eagles, 14 psittacine birds, 4,[15][16][17] Falconiformes, and Accipitriformes. 16 Intraocular pressure as measured by rebound tonometry has been reported in raptors, 18 20 and American flamingos (Phoenicopterusruber).…”
Section: Introductionmentioning
confidence: 99%